Pengaruh Edukasi Ular Tangga Mitigasi Banjir Terhadap Tingkat Pengetahuan Usia 10-12 Tahun Desa Beran Kismoyoso - Dewi Utari; Anjar Nurrohmah (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
The Global Natural Disaster Assessment Report (2019) recorded 49.31% of flood disasters in the world (United Nations Office for Disaster Risk Reduction, 2019.  BNPB recorded 80% of people in the country who are at high risk of disasters, including 200 million people exposed to disaster risk with 107 million of them being of school age. During disasters, children are vulnerable to disease due to weak immune system and insufficient intake of nutritious food at the time of a disaster. Children lose social support, become traumatized.  Knowing the effect of Flood mitigation education through snakes and ladders games on the level of knowledge of flood disaster mitigation Aged 10-12 Years Beran Kismoyoso Ngemplak Boyolali Village. This research is a type of quantitative research with the Pre-Experimental method with the One Group Pre-Test Post-Test Design approach. Sampling of 25 respondents using the Non Probability Sample sampling technique is saturated or all populations are used to be semple.  The data collection technique uses a questionnaire with 25 questions related to self-rescue during flood disasters and knowledge about flood disasters.  Wilcoxon's test results showed a p-value of 0.003<0.05 meaning that there was a difference in the average level of knowledge of flood disaster mitigation before and after being given the snakes and ladders game of flood disaster mitigation.  Based on the results of the study, it shows that there is a significant influence of snakes and ladders game education in increasing knowledge of flood disaster mitigation in children aged 10-12 years in Beran Kismoyoso Ngemplak Boyolali Village.